2022
DOI: 10.1017/s0022050722000274
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Global Financial Cycle: Central Banks as Shock Absorbers in the First Era of Globalization

Abstract: The Classical Gold Standard period, with high capital mobility and fixed-exchange rates, is usually seen as the extreme case of international constraints on monetary policy. Contrary to this view, we show how central bank balance sheets offset the effects of international shocks on domestic interest rates. In contrast, in the United States, a gold standard country without a central bank, the reaction of money market rates was two to four times stronger than that of interest rates in countries with a central ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Convergence to the gold standard in the nineteenth century masked many discontents with the monetary system: John Maynard Keynes (1923, 172) decried it as a "barbarous relic" because of its resource cost and Irving Fisher (1911), like John Law and David Ricardo before him, thought that there were better ways to deliver price stability. Central banks were not merely following the "rules of the game" but engaging in domestically oriented stabilizing policies (Bazot et al, 2022).…”
Section: Narrative Arcmentioning
confidence: 99%
“…Convergence to the gold standard in the nineteenth century masked many discontents with the monetary system: John Maynard Keynes (1923, 172) decried it as a "barbarous relic" because of its resource cost and Irving Fisher (1911), like John Law and David Ricardo before him, thought that there were better ways to deliver price stability. Central banks were not merely following the "rules of the game" but engaging in domestically oriented stabilizing policies (Bazot et al, 2022).…”
Section: Narrative Arcmentioning
confidence: 99%
“…In addition, exchange rates were not passively maintained, but were managed by central banks within narrow bands known as "gold points" (Bordo and MacDonald 1995). Central banks also exerted some influence over interest rates within their own countries, by using their balance sheets to attempt to limit the extent of shocks originating from other countries within the CGS (Bazot, Morys, and Monnet 2022). There were limits to this mission creep, however.…”
Section: Transformation 1: From Coins To Papermentioning
confidence: 99%
“…The well-documented case of Belgium (Ugolini 2012a, 2012b) has paved the way for comparative studies showing, for instance, that central banks in core countries actively sterilised the impact of international shocks deriving from the exogenous rise of the British discount rate (Bazot et al . 2016; Bazot et al 2022). At the periphery this policy of resistance to exogenous shocks was run with less effectiveness, yet studies on Portugal, Scandinavia and Austria have shown how central banks, in general, pursued strong policies of direct intervention aimed at stabilising the exchange rate (Reis 2007; Jobst 2009; Ögren 2012; Øksendal 2012).…”
mentioning
confidence: 99%
“…Before addressing the key issues of this article, an analysis of the pattern of the lira exchange rate is in order; given the depth and strength of commercial and financial links between the two countries, the price in lire of the fully convertible French franc is the most suitable measure to look at. As in the literature the period 1880–1913 is usually divided according to the prevalent exchange rate regime (Cesarano et al 2012; Bazot et al 2022), we present the data 1 desegregated by subperiods, as this also helps better contextualise the specific cases of intervention analysed in the article.…”
mentioning
confidence: 99%
See 1 more Smart Citation